PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP PEMAHAMAN KONSEP MATEMATIS DAN AKTIVITAS BELAJAR PESERTA DIDIK KELAS X IPA SMA ADABIAH PADANG - RAHMAHDANI FADHILLA A (Departemen Matematika, 2020)
Concept understanding is a mathematics basic abilities that helps students improve other mathematics abilities for solve life problems. The test result in class X IPA SMA Adabiah Padang show that the understanding mathematics concept is low. This happens because the lack of students activity during the learning process. One solution is with use Think Talk Write (TTW) learning model. The research purpose is to describe student activities that learn by model TTW and describing whether understanding the mathematial concepts of students studying with TTW model is better than students who study conventionally. This study is a descriptive and quasi experiment with a static group design. Base on observation data analysis and final tests, student activity increase at think stage and fluctuates in others, and understanding mathematical concepts of students studying with TTW model is better than students who study conventionally in class X IPA SMA Adabiah Padang. Keywords — student activity, understanding mathematics concept, TTW.